Bio-ecology and management of Spodoptera frugiperda (Lepidoptera: Noctuidae): A review - Ramzan, Muhammad; Usman, Muhammad; Sajid, Zulnorain; Ghani, Usman; Abdul Basit, Muhammad; Razzaq, Mohsin; Shafee, Waqas; Shahid, Muhammad Rafiq (Journal of Pure and Applied Agriculture, 2023)
Spodoptera frugiperda (Lepidoptera: Noctuidae) locally known as fall armyworm is an emerging pest of various crops (maize, cotton, and sugarcane). It has polyphagous feeding nature and is distributed throughout the globe depending upon the climatic conditions. The cob of maize is its preferred food and is heavily damaged during the high pest population. Feeding of its larvae can cause a characteristic skeletonizing or 'windowing' effect with excessive fecal pellets in maize. Being holometabolous, complete metamorphic changes occur during its developmental process i.e., egg, larva, pupa, and adult. Among all stages, only the larval stage is very dangerous for crop production. At optimum climatic conditions, it completes its life cycle very quickly. Temperature and humidity play an important role in influencing the life cycle duration of the pest. Several control strategies have been adopted by small and large communities or researchers to control this notorious pest